Foreign Reserve Adequacy in Sub-Saharan Africa. (IMF Working Papers; Working Paper ;, 2008)
This paper looks at the question of adequacy of reserves in sub-Saharan African countries in light of the shocks faced by these countries. Literature on optimal reserves so far has not paid attention to the particular shocks facing low-income countries. We use a two-good endowment economy model facing terms of trade and aid shocks to derive the optimal level of reserves by comparing the cost of holding reserves with their benefits as an insurance against a shock. We find that the optimal level of reserves depends upon the size of these shocks, their probability, and the output cost associated with them,.